Will you be my villaintine? (Glendale, California Disney Press, an imprint of Buena Vista Books, Inc., 2020)
So much for true love... Disney Villains do not like Valentine's Day! But what if their loyal sidekicks, the very ones who care about them the most, want to tell their masters just how truly cunning, magnificently wicked, and spectacularly nefarious they are? Why, send them Villaintines instead, of course! Featuring ten evil-doing teams everyone loves to hate--including Ursula and her eels, Scar and his hyenas, Maleficent and her raven, and many more--each spread features sidekicks ' laugh-out-loud Villaintines for their villains.
Ages 6 and up.
108859
Keywords: Valentines -- Juvenile fiction; Villains -- Juvenile fiction; Disney characters -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Fiction; Juvenile works; Picture books